2017
DOI: 10.1111/poms.12749
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturer Rebate Competition in a Supply Chain with a Common Retailer

Abstract: W e consider manufacturer rebate competition in a supply chain with two competing manufacturers selling to a common retailer. We fully characterize the manufacturers' equilibrium rebate decisions and show how they depend on parameters such as the fixed cost of a rebate program, market size, the redemption rate of rebate, the proportion of rebate-sensitive consumers in the market and competition intensity. Interestingly, more intense competition induces a manufacturer to lower rebate value or stop offering reba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Unlike the previous study of asymmetric price leadership scenario in monopoly common retailer channel [3,9], we examine a dual exclusive channel system with and without horizontal Stackelberg competition, where each manufacturer distributes its goods through a single exclusive retailer but two goods are substitute. Moreover, we employ a linear demand based on the utility function of a representative consumer, which has been widely utilized in economics, marketing, and other related literatures [33,45,46]. Our analysis is based on game theory models and reveals several interesting observations and implications by comparing the different subgames.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Unlike the previous study of asymmetric price leadership scenario in monopoly common retailer channel [3,9], we examine a dual exclusive channel system with and without horizontal Stackelberg competition, where each manufacturer distributes its goods through a single exclusive retailer but two goods are substitute. Moreover, we employ a linear demand based on the utility function of a representative consumer, which has been widely utilized in economics, marketing, and other related literatures [33,45,46]. Our analysis is based on game theory models and reveals several interesting observations and implications by comparing the different subgames.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the latest literature, Huang et al [18] suggested that rebate competition among manufacturers or retailers can be studied for future research. Ha et al [19] are the first to consider a multistage game, including two manufacturers selling substitutable products through a common a retailer with slippage effect. Our study is the most close to theirs.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The rebate-sensitive consumers incur a lower redemption cost , and the rebateinsensitive consumers incur a higher redemption cost for the complexity of the redemption steps or their higher cost of time, where 0 ≤ < . We derive the demand functions by following the similar approach from Ha et al [19], which is also developed from Zhang et al [27] and Chung [30]. The utility function of a representative consumer is given by…”
Section: The Benchmark Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of rebates is largely attributable to the seller's ability to price discrimination between consumers with a high and low willingness to pay for a product (Narasimhan, ; Gerstner & Hess, ; Chen, Moorthy, & Zhang, ; Ha, Shang, & Wang, ) . That is, they target only low‐valuation consumers with rebates and charge a higher retail price to high‐valuation consumers.…”
Section: Introductionmentioning
confidence: 99%